Mode of Formation of the Coastal Sabkha Sediments in the Coastal Plain of Al-Dafna Plateau - Mohammed, Ahmed (Scientific Journal for Faculty of Science-Sirte University, 2022)
Two types of sabkhas are distinguished in the study of coastal area; the first type was developed at the mouths of wadis where sea water enters the wadis through high tides; these include; Omm El-Shawesh, Wadi Al-Ain sabkha and Wadi Rizk sabkha. A generalized hydrodynamic model for the formation of this type of sabkha was constructed. The second type of sabkha is stretching behind the dunes, and is divided into a longitudinal strip from east to west where saline crusts appear in some parts and approach the groundwater level. These sabkhas are subjected to flooding during the winter and plant grows within this sabkha. Behind the shore sand hummocks, sea water enters the sabkhas area by seepage and mix with groundwater, and then rises upward to the surface through capillary action and evaporats. This type of sabkha include; Alaqila, Omm Rukbah and Wadi Al-Sawani. The generalized hydrodynamic model suggested for the formation of this kind of sabkha was constructed too.